THYSANOPTERA FOUND IN Prunus persica ORCHARDS IN THE MUNICIPALITY OF ARAUCARIA, PARANÁ - SCHUBER, Joselia Maria; POLTRONIERI, Alex Sandro; ZAWADNEAK, Maria Aparecida Cassilha; CARDOSO, Nerio Aparecido; SOARES, Irani Castro da Silva (Scientia Agraria, 2008)
The objective of this research was to determine which thrips species occur in peach (Prunus persica) and nectarine (Prunus persica var. Nucipersica) orchards. Twenty-four yellow traps, Möericke model, were installed in six peach orchards in the period of July 2005 to September 2006 and in two orchards of nectarine in the period of September to December of 2007. The specimens were collected from the traps weekly and identified. The following species were found in the peach orchards: Arorathrips mexicanus Crawford, 1909; Caliothrips phaseoli Hood, 1912; Ceratothripoides lagoenacollus (Moulton, 1933); Frankliniella insularis Franklin, 1908; Frankliniella occidentalis Pergande, 1895; Frankliniella schultzei (Trybom, 1910); Frankliniella simplex Priesner, 1924; Haplothrips gowdeyi (Franklin, 1908); Haplothrips sp.; and Neohydatothrips sp. The species identified in the nectarine orchards were: Arorathrips fulvus Moulton, 1936, F. insularis, F. occidentalis, F. schultzei, Neohydatothrips sp., Thrips australis Bagnall, 1915; and Thrips tabaci Lindeman, 1889. This study demonstrated the diversity of Thysanoptera with occurrence in stone fruit orchards.